2016
DOI: 10.3390/fi8020025
|View full text |Cite
|
Sign up to set email alerts
|

A Methodological Approach to Evaluate Livestock Innovations on Small-Scale Farms in Developing Countries

Abstract: Abstract:The aim of the study was deepening the knowledge of livestock innovations knowledge on small-scale farms in developing countries. First, we developed a methodology focused on identifying potential appropriate livestock innovations for smallholders and grouped them in innovation areas, defined as a set of well-organized practices with a business purpose. Finally, a process management program (PMP) was evaluated according to the livestock innovation level and viability of the small-scale farms. Logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 24 publications
3
50
0
6
Order By: Relevance
“…These results could indicate the need for deepening the knowledge of smallholders productive logic as their reason for being, their important role in satisfying the food supply and the desire for reducing the vulnerability of risk to poverty (Oosting et al, 2014;Torres et al, 2015). This way, García-Martínez et al (2016) indicate that only 15% of the DP smallholders present commercial objectives and Diaz- Rivera et al (2011) found only 8%.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These results could indicate the need for deepening the knowledge of smallholders productive logic as their reason for being, their important role in satisfying the food supply and the desire for reducing the vulnerability of risk to poverty (Oosting et al, 2014;Torres et al, 2015). This way, García-Martínez et al (2016) indicate that only 15% of the DP smallholders present commercial objectives and Diaz- Rivera et al (2011) found only 8%.…”
Section: Discussionmentioning
confidence: 94%
“…The selection of variables was done through participative methodology proposed by and García-Martínez et al (2016). First, relevant variables were identified in the literature and second, final variables were selected by a group of 14 experts composed by researchers and livestock service providers.…”
Section: Selection Of Variables and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The technological level of the farms was evaluated according to the methodological approach used by [5,15,16]. The selection of innovations and its grouping into technological areas took place according to a qualitative, consensus, and participatory methodology described by [17]. Briefly, the methodology consists of two steps.…”
Section: Livestock Innovation Levelmentioning
confidence: 99%
“…The first article, A Methodological Approach to Evaluate Livestock Innovations on Small-Scale Farms in Developing Countries authored by Antón García-Martínez, José Rivas-Rangel, Jaime Rangel-Quintos, José Antonio Espinosa, Cecilio Barba and Carmen de-Pablos-Heredero [1], analyses the knowledge of livestock innovations on small-scale farms in developing countries and confirms that implementing an intelligent system improves the viability of farms by an additional 21%, due to a better integration of processes, resulting in more efficient management.…”
mentioning
confidence: 99%